Forced Migration Governance in Southeast Asian Countries: ‘Same but Different’? - Muhammad Riza Nurdin; Mala Rajo Sathian; Hanafi Hussin (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
This paper examines the governance of forced migration in Southeast Asia. The region hosts about 2.5 million of forcibly displaced migrants from a worldwide total of 70 million (2018). The migrants include intra- ASEAN and non-ASEAN refugees or asylum seekers, notably from the Middle East. Based on a review of recent literature, the paper investigates three main destination states in SEA that host the majority of the forced migrants; Indonesia, Malaysia, and Thailand. The paper examines (i) local policies in the governance of forced migrants and (2) the practice of non-refoulement principle. The findings reveal that in terms of forced migration governance, Indonesia, Malaysia, and Thailand are ‘same but different'; meaning that despite being similar, each country produces different outcomes.